Effect of Germination on the Nutritional Properties, Phytic Acid Content, and Phytase Activity of Quinoa (Chenopodium quinoa Willd) - Pedro Maldonado-Alvarado; Darío Javier Pavón-Vargas; Juan Abarca-Robles; Silvia Valencia-Chamorro; Claudia Monika Haros (Foods, 2023)
The aim of this study is to evaluate the effect of desaponification, soaking, germination, and refrigerated storage on the phytase activity, phytic acid content, and nutritional properties of three varieties of quinoa: white, red, and black. Desaponification and soaking reduced the number of minerals and the nutritional content. Germination of the seeds was carried out in the desaponified samples. The nutritional values, phytase activity, and phytic acid content of quinoa were measured after 6 h of soaking and then at 4 and 7 days during germination plus 7 days of refrigerated storage (4 °C). Germination increased the fibre and protein content as well as the iron, zinc, and calcium content. Germination significantly increased the phytase activity in all varieties and decreased the phytic acid content. The phytic acid content decreased during germination from 32 to 74%. Refrigerated storage had no significant effect on most of the factors studied. Germination boosts nutritional content and phytase activity while decreasing phytic acid content. Germination can be a simple method to reduce phytic acid in quinoa and may also improve the nutritional quality of this pseudocereal with the potential for use in functional foods and vegetarian diets.